KETERWAKILAN PEREMPUAN PADA LEMBAGA LEGISLATIF SEBAGAI UPAYA KESETARAAN GENDER DI JAWA TIMUR - Radhiyah Rahma Kartika; Regita Aprilia; Moch Ali Mashuri (Jurnal Penelitian Administrasi Publik, 2021)
Indonesia is a large archipelagic country and has approximately 17,000 islands. As the largest archipelago country, Indonesia has a diversity of both geographical location, population, culture, and even in terms of politics. Existing diversity makes Indonesia a democratic country, where the Indonesian state adheres to the principles of the people, for the people, and by the people. This principle can be concluded that in Indonesia the government carried out comes from the people and is intended for the people. The same right to participate in managing the state is applied to the political system in the Indonesian state. However, in reality the political system that exists in Indonesia still has gender equality discrimination. Law Number 2 of 2008 concerning Political Parties, and Law Number 10 of 2008 mandates the need for political education by taking into account gender justice and equality. The purpose of this study is to analyze and describe the representation of women in legislative institutions as an effort of gender equality in East Java, using qualitative research methods with literature review data collection techniques, and data analysis by presenting data, and drawing conclusions. The location of this research is in the Regional Representative Council of East Java Province. The results obtained by the study are that the participation of women in politics today is more positive. However, the increase in the number of women councilors from period to period has not been able to rid people of gender inequality experienced.